Partisipasi Masyarakat dalam Meningkatkan Good Governance di Tingkat Desa - Irma Sunarty Purba; Djanius Djamin (Universitas Medan Area, 2015)
This study aims to determine the participation of rural communities in improving good governance, and the relationship village participation in promoting Good Governance. This research was conducted in the village of Aras Kabu Lubukpakam Beringin Subdistrict of Deli Serdang. Methods now used is quantitative analysis. The data collection tools used were observation, distributing questionnaires (questionnaire) and interview. The total population of 720 families, while the respondents to have taken 10% of the total population of the 72 households. The sampling technique used is that of the sample random sample randomly from different populations livelihoods as farmers, Self, and Civil Servants (PNS). Data analysis techniques used in this research is the analysis of the percentage and then the data is processed by using the correlation coefficient with the product moment formula. From the test results obtained by the hypothesis, that there is a positive relationship between community participation to improve Good Govenance at the village level Aras Kabu Lubukpakam Beringin Subdistrict of Deli Serdang. This is evidenced by the t is equal to 9.966. Values t is greater than t table that is equal to 9.966> 1.966 (with interpolation) at significance level of 5% on the degree of freedom (df) = n-2 (72-2) = 70 then Ho is rejected and Ha accepted.